2017
DOI: 10.1021/acs.iecr.6b03748
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence and Energy Transfer of Dual-Emitting Solid Solution Phosphors (Ca,Sr)10Li(PO4)7:Ce3+,Mn2+ for Ratiometric Temperature Sensing

Abstract: A series of novel dual-emitting solid solution phosphors, (Ca,Sr) 10 Li(PO 4 ) 7 :Ce 3+ , Mn 2+ (CSLP:Ce 3+ ,Mn 2+ ), were synthesized by high-temperature solid-state method. CSLP:Ce 3+ ,Mn 2+ exhibits both Ce 3+ violet emission and Mn 2+ red emission under UV excitation. It is found that Sr 2+ partial substitution of Ca 2+ could result in enhancement of Mn 2+ emission intensity and blue-shift of Mn 2+ emission wavelength, which is due to site symmetry reduction and polyhedron expansion, respectively. The Ce 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(34 citation statements)
references
References 31 publications
0
34
0
Order By: Relevance
“…In most cases, realization of single Eu 2+ , Ce 3+ , Bi 3+ , or Mn 2+ ion doped tunable solid solutions is based upon how to manipulate isostructural ions that feature the same valence but different radii at the same coordination number (CN). For example, Ji et al reported the Ce 3+ tunable emission in the Ba2-xSrxSiO4:Ce 3+ (x = 0 → 1.8, λem = 391 → 411 nm) [18]; Fu et al reported the Eu 2+ tunable emission in the Sr2.97-xBaxMgSi2O8:Eu 2+ ,Dy 3+ (x = 0 → 2.0, λem = 434 → 464 nm) [19]; Dai et al showed the Eu 2+ tunable emission in the (K1-x,Nax)SrPO4:Eu 2+ (x = 0 → 0.6, λem = 446 → 498 nm) [20]; Zhang et al realized and presented the Mn 2+ tunable emission in the (Ca1-aSra)10Li(PO4)7:0.09Mn 2+ (a = 0 → 0.4, λem = 642 → 632 nm) [21]; and Kang et al recently reported the (Yx,Luy,Scz)VO4:Bi 3+ (x → y → z; λem = 566 → 576 → 635 nm) tunable solid solution [22].…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, realization of single Eu 2+ , Ce 3+ , Bi 3+ , or Mn 2+ ion doped tunable solid solutions is based upon how to manipulate isostructural ions that feature the same valence but different radii at the same coordination number (CN). For example, Ji et al reported the Ce 3+ tunable emission in the Ba2-xSrxSiO4:Ce 3+ (x = 0 → 1.8, λem = 391 → 411 nm) [18]; Fu et al reported the Eu 2+ tunable emission in the Sr2.97-xBaxMgSi2O8:Eu 2+ ,Dy 3+ (x = 0 → 2.0, λem = 434 → 464 nm) [19]; Dai et al showed the Eu 2+ tunable emission in the (K1-x,Nax)SrPO4:Eu 2+ (x = 0 → 0.6, λem = 446 → 498 nm) [20]; Zhang et al realized and presented the Mn 2+ tunable emission in the (Ca1-aSra)10Li(PO4)7:0.09Mn 2+ (a = 0 → 0.4, λem = 642 → 632 nm) [21]; and Kang et al recently reported the (Yx,Luy,Scz)VO4:Bi 3+ (x → y → z; λem = 566 → 576 → 635 nm) tunable solid solution [22].…”
Section: Introductionmentioning
confidence: 99%
“…Whitlockite β‐Ca 3 (PO 4 ) 2 and its derivatives have been extensively investigated because of their ferroelectric properties, their use for bioceramic applications, and their utility as potential phosphors for w‐LEDs . So far, some Ca 3 (PO 4 ) 2 luminescence materials, such as Ca 8 MgLu(PO 4 ) 7 : Ce 3+ , Tb 3+ , Mn 2+ , (Ca,Sr) 10 Li(PO 4 ) 7 : Ce 3+ , Mn 2+ , and Ca 8 MgY(PO 4 ) 7 : Eu 2+ , Mn 2+ have been widely studied . Moreover, Ca 8 ZnLa(PO 4 ) 7 : Eu 2+ , Mn 2+ phosphor, whose luminescence properties and energy transfer have been reported by Liu and coworkers .…”
Section: Introductionmentioning
confidence: 99%
“…The maximum values of S a and S r are calculated to be 0.118 K −1 (473.15 K) and 0.795% K −1 (448.15 K), respectively. It is a good set of values, compared to many previous studies . So, Bi 3+ ‐Eu 3+ co‐doped LaScO 3 phosphor have good optical thermometric performance.…”
Section: Resultsmentioning
confidence: 99%